Pengaruh Jumlah Penduduk Miskin, Rata – Rata Lama Sekolah dan Tingkat Partisipasi Angkatan Kerja terhadap Tingkat Pengangguran Terbuka di Provinsi Maluku Tahun 2017-2023 (Pendekatan Data Panel) - Bela Saputri; Muhammad Afdal Samsuddin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to examine the influence of the number of poor people, average years of schooling, and labor force participation rate on the open unemployment rate (OUR) in Maluku Province from 2017 to 2023. The study uses panel data from 11 districts/cities and applies a regression model using a fixed effect approach. The results show that the average years of schooling have a positive and significant effect on the open unemployment rate. This implies that the longer an individual pursues education, the higher the likelihood of unemployment, as they tend to have higher job expectations and are less willing to accept available jobs. Meanwhile, the labor force participation rate has a negative and significant effect, indicating that a higher number of actively working individuals leads to a lower unemployment rate. The number of poor people does not have a significant effect on unemployment. Overall, the model explains approximately 53.5% of the variation in the open unemployment rate. These findings indicate that education and labor participation are crucial factors in reducing unemployment, but must be supported by the availability of suitable employment opportunities.